2022
DOI: 10.1097/jxx.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the outcomes of YAG laser anterior capsulotomies performed by an advanced nurse practitioner to ophthalmologists in the management of anterior capsular contraction syndrome

Abstract: Background:Anterior capsular contraction syndrome (ACCS) describes the progressive fibrotic phimosis of the anterior capsular bag that usually occurs a few months after cataract surgery. YAG laser anterior capsulotomy (YAGAC) is the most common treatment option due to the low-risk profile of this intervention.Purpose:In this series, we evaluated the outcomes of an advanced nurse practitioner (ANP) in conducting this laser intervention, comparing the results with those of ophthalmologists.Methodology:Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It utilizes the shockwave produced by the resulting explosion to disrupt and disintegrate the tissue. This makes it an ideal non-surgical choice for treating ACCS ( 104 ). Hayashi et al ( 105 ) analyzed the anterior capsulotomy area before and after Nd:YAG laser capsulotomy in 32 eyes, and found that contrast sensitivity at most visual angles significantly improved following the procedure.…”
Section: Interventions For Accsmentioning
confidence: 99%
“…It utilizes the shockwave produced by the resulting explosion to disrupt and disintegrate the tissue. This makes it an ideal non-surgical choice for treating ACCS ( 104 ). Hayashi et al ( 105 ) analyzed the anterior capsulotomy area before and after Nd:YAG laser capsulotomy in 32 eyes, and found that contrast sensitivity at most visual angles significantly improved following the procedure.…”
Section: Interventions For Accsmentioning
confidence: 99%